Training & develpoment: linking up theoretical knowledg with practical experience in ACI Logistics Limited (SHWAPNO) - Prince, Md.Tanvir Ahmed (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Masters of Business Administration, 2018.